Can attention to the intestinal microbiota improve understanding and treatment of anorexia nervosa?. (3rd May 2016) - Carr, Jacquelyn; Kleiman, Susan C.; Bulik, Cynthia M.; Bulik-Sullivan, Emily C.; Carroll, Ian M.
ABSTRACT: Anorexia nervosa (AN) is characterized by severe dietary restriction or other weight loss behaviors and exhibits the highest mortality rate of any psychiatric disorder. Therapeutic renourishment in AN is founded primarily on clinical opinion and guidelines, with a weak evidence base. Genetic factors do not fully account for the etiology of AN, and non-genetic factors that contribute to the onset and persistence of this disease warrant investigation. Compelling evidence that the intestinal microbiota regulates adiposity and metabolism, and more recently, anxiety behavior, provides a strong rationale for exploring the role of this complex microbial community in the onset, maintenance of, and recovery from AN. This review explores the relationship between the intestinal microbiota and AN and a potential role for this enteric microbial community as a therapy for this severe illness.